QUANTITATIVE ASSESSMENT SOFTWARE DEVELOPMENT FOR THE CHLORELLA VULGARIS MICROALGAE POPULATION - НОВАК, Д. С.; CУКАЛО М. Л. (Technologies and Engineering, 2024)
Purpose. Software development to quantify the population growth for the microalgae Chlorella. Methods. Software was developed using Python programming language, external libraries: Numpy, Xlsxwriter, Matplotlib and PIL. The developed software suitability to quantify the population growth of the microalgae Chlorella and its verification was determined. During this verification, the population growth of the microalgae with different stages of biomass growth were evaluated. Samples of the microalgae Chlorella were obtained over a period of several weeks’ population growth. Results. Software that allows estimating the population growth of the microalgae Chlorella in the aquatic environment has been developed. Using this software, data dependence of the heterogeneity coefficient of microalgae Chlorella vulgaris biomass growth was obtained. The population growth leads to a decrease in this heterogeneity. This effect can be due the optimal conditions presence for the cultivation of microalgae Chlorella vulgaris. Scientific novelty. The effect of microalgae Chlorella population growth on the system homogeneity has been determined. The increase of microalgae Chlorella vulgaris biomass content within 4 weeks leads to coefficient of heterogeneity decrease from 92% to 47%, due to the aggregation of microalgae Chlorella vulgaris in the aquatic environment. Practical significance. Developed software allows quantify the growth of the microalgae Chlorella vulgaris population in the aquatic environment and can be used to control the algae biomass rise in industrial production. Conclusion. Software that allows assessing the uniformity distribution of Chlorella vulgaris microalgae biomass population growth has been developed. It is applicable to study the level of microorganisms’ concentration in the aquatic environment. The results of its verification indicate the developed software suitability for practical use. Using the developed software, the influence of Chlorella vulgaris microalgae biomass population growth in the aquatic environment was determined. It is shown that microalgae Chlorella vulgaris population growth from 1 to 4 weeks leads to decrease in the mixing index from 93% to 47%, which is due optimal conditions presence for the cultivation of the microalgae Chlorella vulgaris. The research methodology can be used in the automated monitoring complexes development for the ecological state of water resources and for controlling the industrial production microalgae Chlorella vulgaris population.